Diabetic Personal Health Record: A Systematic Review Article - Amirabbas AZIZI; Robab ABOUTORABI; Zahra MAZLOUM-KHORASANI; Benyamin HOSEINI; Mahmood TARA (Tehran University of Medical Sciences, 2016)
Background: Diabetes disease is one of the 4 main types of non-communicable diseases. No research has been conducted in order to identify data items for Diabetic Personal Health Record (DPHR), in Iran. This study, with the aim of systematically developing the DPHR was done to supply ultimately the country with a national model through Delphi method. Methods: We conducted a systematic review of the literature using the following electronic databases: PubMed, Web of sciences, Scopus, Science Direct, and ACM digital library. The year of the study included the obtained articles was 2013. We used a 3-step method to identify studies related to DPHR. Study selection processes were performed by two reviewers independently. The eligible studies were included in this review. Quality of studies was assessed using a mixed approach scoring system. Reviewers used 2-step method for the validation of the final DPHR model. Results: Initially, 2011 papers were returned from online databases and 186 studies from gray literature search. After removing duplicates, study screening, and applying inclusion and exclusion criteria, 129 studies were eligible for further full-text review. Considering the full-text review, 34 studies were identified for final review. Given the content of selected studies, we determined seven main classes of DPHR. The highest score belongs to home monitoring data class by mean of 19.83, and the lowest was general data class by mean of 3.89. Conclusion: Together with representative sample of endocrinologist in Iran achieved consensus on a DPHR model to improve self-care for diabetic patients and to facilitate physician decision making.